Plant-Soil Relationships of Bromus tectorum L.: Interactions among Labile Carbon Additions, Soil Invasion Status, and Fertilizer - Robert R. Blank; James A. Young (Applied and Environmental Soil Science)
Invasion of western North America by the annual exotic grass Bromus tectorum L. (cheatgrass) has been an ecological disaster. High soil bioavailability of nitrogen is a contributing factor in the invasive potential of B. tectorum. Application of labile carbon sources to the soil can immobilize soil nitrogen and favor native species. We studied the interaction of labile carbon addition (sucrose), with soil invasion status and fertilizer addition on the growth of B. tectorum. Soils were noninvaded (BNI) and B. tectorum invaded (BI). Treatments were control, sucrose, combined fertilizer, and sucrose + fertilizer. The greenhouse experiment continued for 3 growth-cycles. After the 1st growth-cycle, sucrose addition reduced B. tectorum aboveground mass almost 70 times for the BI soil but did not significantly reduce growth in the BNI soil. B. tectorum aboveground mass, after the 1st growth-cycle, was over 27 times greater for BI control soils than BNI control soils. Although sucrose addition reduced soil-solution NO3−, tissue N was not significantly lowered, suggesting that reduction of soil available N may not be solely responsible for reduction in B. tectorum growth. Noninvaded soil inhibits growth of B. tectorum. Understanding this mechanism may lead to viable control strategies.